The Application of Counter-Rotating Turbine in Rocket Turbopump - Tang Fei; Zhao Xiaolu; Xu Jianzhong (International Journal of Rotating Machinery)
Counter rotating turbine offers advantages on weight, volume, efficiency, and maneuverability relative to the conventional turbine because of its special architecture. Nowadays, it has been a worldwide research emphasis and has been used widely in the aeronautic field, while its application in the astronautic field is seldom investigated. Researches of counter rotating turbine for rocket turbopump are reviewed in this paper. A primary analysis of a vaneless counter rotating-turbine configuration with rotors of different diameters and rotational speeds is presented. This unconventional configuration meets the requirements of turbopump and may benefit the performance and reliability of rocket engines.